A Genetic Algorithm for the Double Row Layout Problem - Rifai, Achmad Pratama; Windras Mara, Setyo Tri; Kusumastuti, Putri Adriani; Wiraningrum, Rakyan Galuh (Institute of Research and Community Outreach - Petra Christian University, 2020)
The double row layout problem (DRLP) is an NP-hard and has many applications in the industry. The problem concerns on arranging the position of machines on the two rows so that the material handling cost is minimized. Although several mathematical programming models and local heuristics have been previously proposed, there is still a requirement to develop an approach that can solve the problem efficiently. Here, a genetic algorithm is proposed, which is aimed to solve the DRLP in a reasonable and applicable time. The performances of the proposed method, both its obtained objective values and computational time, are evaluated by comparing it with the existing mathematical programming model. The results demonstrate that the proposed GA can find relatively high-quality solutions in much shorter time than the mathematical programming model, especially in the problem with large number of machines.